Pengaruh Konten Channel Youtube Nihongo Manttapu Terhadap Pemilihan Karir Generasi Z (Studi Pada SMA Negeri 1 Bangsal) - Suyanto, Devi Anggraeni; Zusyana Dewi, Ratnaningrum; Hayau Lailin, M.I.Asyarin (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2021)
The activities of internet users in Indonesia are dominated by Generation Z, namely the generation born in 1997 to 2010. Generation Z uses YouTube as an entertainment medium as well as to add insights and knowledge that are not found in knowledge books about something they are interested in. Jerome Polin is one of the young YouTubers who is active in providing educational-themed content among the younger generation such as how to learn Japanese, college life in Japan battles general knowledge, tips and tricks to learn math formulas, etc. This study was conducted to measure how much influence Nihongo Manttapu's YouTube channel content has on the career choice of generation Z with the variables between the socioeconomic level of parents and the frequency of watching content. This research uses new media theory, source credibility theory, media dependency and social learning theory. The approach used in this research is quantitative, with a survey method using an e-questionnaire distributed to 130 students who are the research sampling, which is then carried out by a simple linear regression test, multiple linear regression test and hypothesis testing. The results showed that YouTube Channel Content has a significant positive effect on Generation Z's Career Selection, where the expertise, trust and attractiveness of communicators is one of the important factors why Generation Z watches Nihongo Manttapu's YouTube Channel content in addition to informative and entertaining content. The majority of students claim to access Jerome's YouTube channel content because they have the same interests, after watching Jerome's content students are motivated to further develop their interests in any field, they have dreams or careers according to their interests and always feel happy after watching Nihongo Manttapu's content.